Cover Image. (24th January 2023) - Tafreshi, Omid Aghababaei; Saadatnia, Zia; Ghaffari‐Mosanenzadeh, Shahriar; Okhovatian, Sogand; Park, Chul B.; Naguib, Hani E.
Abstract : The cover image is based on the Research Article Machine learning‐based model for predicting the material properties of nanostructured aerogels by Omid Aghababaei Tafreshi et al., https://doi.org/10.1002/pls2.10082 (The cover image was created using BioRender.com )